Soft skills in expatriation - Silva, Susana (2018)
Contemporary competitiveness and globalisation drives organisations to explore new markets, and provide themselves with distinctive features and value added. Additionally, the literature underlines the importance of this global environment impact the processes of managing Human resources in organisations. Therefore, the adequacy of human resources is imperative in the strategy of organisations. This study aims to understand the importance of the international assignment, to understand the soft skills most valued by recruiters and how is their evaluation. To successfully address these aims we conducted a qualitative study. The data collection method used was semi-structured interview and were interviewed ten recruiters of expatriates. Data were analysed according to content analysis procedures The results suggest that soft skills are important features in the international assignment, since that act on factors that influence the success of the assignment. The most important skills are interpersonal relationships, teamwork, communication, adaptability and tolerance to ambiguity. We discuss the main practical and theoretical implications, and offer some suggestions for further studies.